373 Protective role of conization before radical hysterectomy in early-stage cervical cancer: a propensity-score matching study. (13th November 2020) - Bizzarri, N; Pedone Anchora, L; Kucukmetin, A; Ratnavelu, N; Korompelis, P; Carbone, MV; Fedele, C; Bruno, M; Vizzielli, G; Gallotta, V; De Vincenzo, R; Chiantera, V; et al.
Abstract : 3 Department of Gynecologic Oncology, ARNAS Ospedali Civico Di Cristina Benfratelli, University of Palermo, Italy Introduction: The aim of this study was to assess the prognostic role and the peri-operative outcomes of conization performed before radical hysterectomy in early-stage cervical carcinoma. Methods: Multi-center retrospective observational cohort study including patients with FIGO 2009 IB1 cervical carcinoma treated with radical hysterectomy between 06/2004 and 06/2019. Patients were divided into two groups according to conization before radical surgery. One-to-one case–control matching was used to adjust the baseline characteristics. Results: 332 patients were included after propensity matching (166, 50% in each group) (table 1 ). 24/166 (14.4%) and 142/166 (85.6%) conization patients had negative and positive surgical margins on the conization specimen, respectively. No difference in intra- and post-operative complications was noted between the two groups (p=0.542 and p=0.180, respectively). Patients undergoing conization before radical hysterectomy, received less adjuvant treatment (p<0.001) and had a better 5-year disease-free survival (DFS) than patients who did not receive conization (89.8% versus 80.0%, respectively; p=0.010) (figure 1 ). No difference in 5-year overall survival (OS) (97.1% versus 91.4%, respectively; p=0.114) and in recurrence pattern (p=0.115) was reported between the two groups. Factors significantly independently related to higher risk of recurrence were pathologic tumor diameter >20 mm and no conization before radical hysterectomy (p=0.011 and p=0.018, respectively). The only independent variable influencing OS was pathologic tumor diameter >20 mm (p=0.020). Conclusions: Conization before radical hysterectomy was associated with improved DFS and lower probability of receiving adjuvant treatment in patients with FIGO-stage IB1 cervical cancer. No difference in peri-operative complications and OS was noted in these groups of patients.